Adventures in the fish trade - Williams, David M.; Gill, Anthony C. (Zootaxa, 2011)
The Systematics Association (SA), a London based organisation dedicated to the promotion of systematic (comparative) biology in all its various aspects, was founded in May 1937. It is based on objectives set out for its earlier incarnation, the “Committee on Systematics in Relation to General Biology” (some relevant history can be found in Winsor 2000). That group’s remit was, and the SA’s still is, “to provide a forum for the discussion of the general theoretical and practical problems of taxonomy” (http://www.systass.org ; see also Nature 140:163, 1938).